Saxifraga moschata Wulfen v SLoveniji - Praprotnik, Nada (Scopolia, 1982)
The territory of the Socialist Republic of Slovenia offers favourable conditions to three subspecies of Saxifraga moschata WULFEN: S. moschata WULF.subsp. Moschata, S. moschata WULF. subsp. Atropurpurea (STERNB.) N. PRAPROTNIK and S. moschata WULF. subsp. Carniolica (HUTER) T. WRABER. For all of said subspecies there are stated the data on morphologic features, growth areas, and habitats with areal charts.
Keywords: botanika; botany; Rhododendron-Park Bremen; vegetacija; vegetation; Slovenia; Slovenija